NILAI PENDIDIKAN PADA KESENIAN TRADISIONAL IRING-IRING DAMAR KURUNG DALAM PERSPEKTIF HERMENEUTIKA PAUL RICOEUR (SUATU TINJAUAN BUDAYA PADA MASYARAKAT KECAMATAN ASTANAJAPURA KABUPATEN CIREBON) - Nur Syamsiyah (Sosio-Didaktika: Social Science Education Journal, 2020)
This study aims to explore and describe the educational value from the traditional art of Iring-iring Damar Kurung in Astanajapura sub-district, Cirebon Regency under Paul Ricoeur's hermeneutic theory. This research is a qualitative method employing a phenomenological approach. The results findings and conclusions of this study revealed that the educational values in the art of the procession of Iring-iring Damar Kurung in Astanajapura are in accordance with Education Ministry Act Number 20 of 2018 regarding strengthening of Educational Character (Penguatan Pendidikan Karakter/PPK) as described in Presidential Decree Number 87 of 2017. Thus, in procession of the traditional art, Damar Kurung showed some educational values such as (1) religious values, (2) independence, (3) nationalism, (4) mutual cooperation, and (5) integrity. In addition to that, the symbols and meanings of this art are (1) nine decorative lights, symbolizing Wali Songo as a symbol of the spread of Islam in Indonesia, especially in the Java Island, (2) the umbrella is a symbol of protection, (3) Pedicab Stage is a symbol of honor, (4) genjring has a symbol of preaching the spread of Islam in Cirebon, (5) nine children carrying decorative lights are symbols of mutual cooperation, (6) night means dark or a symbol of ignorance, and (7) reading sholawat is a symbol of blessing and savior.Keywords: The educational values, traditional arts, Iring-iring Damar Kurung, Paul Ricoeur’s hermeneutics theory